Basis Teologis Partnership dalam Misi Kristen: Menilik Problem Partnership dalam Misi Kristen Masa Kini serta Evaluasinya - Karo, Dinar Br; Blegur, Romelus (SCRIPTA: Jurnal Teologi dan Pelayanan Kontekstual, 2023)
The purpose of this study is to re-emphasize the importance of partnership from a Christian theological perspective, that partnership initiated by the Triune God and the church or believer must be based on that basis. Partnerships are now increasingly narrowed in their realization so that a re-evaluation is needed with theological and Biblical foundations. This research uses descriptive qualitative research methods with reference to literary sources that are relevant to the subject of this research. The findings in this study to answer the problem of partnership in Christian mission are that partnership must be global and universal, must plunge into the boundaries of the organization that governs it, and be based on the ultimate relationship of the Triune God.